Increasing the species diversity of the monotypic genus Pariolius Cope 1872 (Siluriformes: Heptapteridae) after more than 150 years - Faustino-Fuster, Dario R.; López-Castaño, Jeisson A.; Quiñones, Jhonatan M.; Meza-Vargas, Vanessa (Zootaxa, 2024)
Pariolius is a heptapterid genus represented by P. armillatus that is distributed along the upper Amazon River basin. A taxonomic integrative revision of Pariolius from Colombian Rivers revealed two new species. Several approaches as morphological, morphometric, meristic, osteology and molecular data were used to distinguish between Pariolius species. The two new species are distinguished from congeners by the caudal-fin shape and numbers of rays, colorations patterns and several morphometric characters. The two new species of Pariolius are restricted to tributaries of the Upper Orinoco and Upper Negro rivers in Colombia.